An Introduction to moral theology - May, William E., 1982-- (Hunting, Ind : Our Sunday Visitor Pub, 1991)
An Introduction to moral theology presents, clearly and cogently, the basic moral teaching of the church and the foundations for this teaching. Thorougly in accord with the thought of Vatican Council II, this stimulating work examines our moral life as an effort to discover who we are and how we can become the complete beings God wants us to be. This book begins by focusing on humans and their ability to define their own lives through self-determining choices. After proving the meaning of conscience and its indispensable role in our search for moral truth, it examines, in depth, the meaning of natural law in light of the teaching of St. Thomas Aquinas, Vatican II and the thought of contemporary theologians.
The church as moral teacher